Optimal energy management for a hybrid energy storage system combining batteries and double layer capacitors - Romaus, C.; Bocker, J.; Witting, K.; Seifried, A.; Znamenshchykov, O. (2009 IEEE Energy Conversion Congress and Exposition)

Energy transfer via linear doubly-fed motor in different operating modes - Schneider, T.; Schulz, B.; Henke, C.; Witting, K.; Steenken, D.; Bocker, J. (2009 IEEE International Electric Machines and Drives Conference)

Designing optimal low-thrust gravity-assist trajectories using space pruning and a multi-objective approach - Schütze, Oliver; Vasile, Massimiliano; Junge, Oliver; Dellnitz, Michael; Izzo, Dario (Engineering Optimization)

Multi-objective shape optimization for piezoceramics - Wang, Fang; Dellnitz, Michael (2008 Symposium on Piezoelectricity, Acoustic Waves, and Device Applications)

Kompensation der „Banken-Krise“ durch das Anlageberatungsrecht - Krimphove, Dieter (Finanz Betrieb)

Comparing Architectural Styles for Service-Oriented Architectures – a REST vs. SOAP Case Study - Becker, Jörg; Matzner, Martin; Müller, Oliver (Information Systems Development)

Documentation of flexible business processes-A healthcare case study - Becker, Jörg; Bergener, Katrin; Müller, Oliver; Müller-Wienbergen, Felix (Americas Conference on Information Systems)

A design research study on enhancing creativity-The case of developing product-service bundles - Müller-Wienbergen, Felix; Seidel, Stefan; Müller, Oliver; Knackstedt, Ralf; Becker, Joerg (European Conference on Information Systems)

Towards multi-movement hand prostheses: Combining adaptive classification with high precision sockets - Boschmann, Alexander; Kaufmann, Paul; Platzner, Marco; Winkler, Michael (Proc. Technically Assisted Rehabilitation (TAR))

Evolvable Robot Controller - Kostin, Alexander

ReconOS: Multithreaded Programming for Reconfigurable Computers - Lübbers, Enno; Platzner, Marco (ACM Transactions on Embedded Computing Systems)
Keywords: Reconfigurable computing; multithreading; operating systems

Compiler for a Custom Instruction Set CPU - Tofall, Martin

Coarse-grained CGP Model using Xilinx Virtex5 DSP48E Functional Units - Warkentin, Alexander

Implementierung von Kryptographie-Hardwarebeschleunigern für das HW/SW-Betriebssystem ReconOS - Wildenhain, Benedikt

Signature Self Checking (SSC): A Low-Cost Reliable Control Logic for Pipelined Microprocessors - Ghasemzadeh Mohammadi, Hassan; Miremadi, Seyed Ghassem; Ejlali, Alireza (Dependable Computing (PRDC), 2009 IEEE Pacific Rim International Symposium on)

Robust vehicle localization based on multi-level sensor fusion and online parameter estimation - Bevermeier, Maik; Peschke, Sven; Haeb-Umbach, Reinhold (6th Workshop on Positioning Navigation and Communication (WPNC 2009))
In this paper we present a novel vehicle tracking algorithm, which is based on multi-level sensor fusion of GPS (global positioning system) with Inertial Measurement Unit sensor data. It is shown that the robustness of the system to temporary dropouts of the GPS signal, which may occur due to limited visibility of satellites in narrow street canyons or tunnels, is greatly improved by sensor fusion. We further demonstrate how the observation and state noise covariances of the employed Kalman filters can be estimated alongside the filtering by an application of the Expectation-Maximization algorithm. The proposed time-variant multi-level Kalman filter is shown to outperform an Interacting Multiple Model approach while at the same time being computationally less demanding.
Keywords: covariance matrices; expectation-maximisation algorithm; expectation-maximization algorithm; global positioning system; Global Positioning System; GPS; inertial measurement unit; interacting multiple model approach; Kalman filters; multilevel sensor fusion; narrow street canyons; narrow tunnels; online parameter estimation; parameter estimation; road vehicles; robust vehicle localization; sensor fusion; state noise covariances; time-variant multilevel Kalman filter; vehicle tracking algorithm

Joint Parameter Estimation and Tracking in a Multi-Stage Kalman Filter for Vehicle Positioning - Bevermeier, Maik; Peschke, Sven; Haeb-Umbach, Reinhold (IEEE 69th Vehicular Technology Conference (VTC 2009 Spring))
In this paper we present a novel vehicle tracking method which is based on multi-stage Kalman filtering of GPS and IMU sensor data. After individual Kalman filtering of GPS and IMU measurements the estimates of the orientation of the vehicle are combined in an optimal manner to improve the robustness towards drift errors. The tracking algorithm incorporates the estimation of time-variant covariance parameters by using an iterative block Expectation-Maximization algorithm to account for time-variant driving conditions and measurement quality. The proposed system is compared to an interacting multiple model approach (IMM) and achieves improved localization accuracy at lower computational complexity. Furthermore we show how the joint parameter estimation and localizaiton can be conducted with streaming input data to be able to track vehicles in a real driving environment.
Keywords: computational complexity; expectation-maximisation algorithm; Global Positioning System; inertial measurement unit; inertial navigation; interacting multiple model; iterative block expectation-maximization algorithm; Kalman filters; multi-stage Kalman filter; parameter estimation; road vehicles; vehicle positioning; vehicle tracking

Eine Plattform fuer Mehrwertdienste im Bereich Logistik - Drahtlose Fahrzeug- und Laderaumueberwachung fuer LKW mit Hilfe einer Maut-On-Board Unit - Bevermeier, Maik; Peschke, Sven; Haeb-Umbach, Reinhold (DGON Navigationskonvent 2009)

Model based feature enhancement for automatic speech recognition in reverberant environments - Krueger, Alexander; Haeb-Umbach, Reinhold (Interspeech 2009)
In this paper we present a new feature space dereverberation technique for automatic speech recognition. We derive an expression for the dependence of the reverberant speech features in the log-mel spectral domain on the non-reverberant speech features and the room impulse response. The obtained observation model is used for a model based speech enhancement based on Kalman filtering. The performance of the proposed enhancement technique is studied on the AURORA5 database. In our currently best configuration, which includes uncertainty decoding, the number of recognition errors is approximately halved compared to the recognition of unprocessed speech.

On the Estimation and Use of Feature Reliability Information for Noise Robust Speech Recognition - Leutnant, Volker; Haeb-Umbach, Reinhold (International Conference on Acoustics (NAG/DAGA 2009))
In this paper we present an Uncertainty Decoding rule which exploits feature reliability information and interframe correlation for noise robust speech recognition. The reliability information can be obtained either from conditional Bayesian estimation, where speech and noise feature vectors are tracked jointly, or by augmenting conventional point estimation methods with heuristics about the estimator's reliability. Experimental results on the AURORA2 database demonstrate on the one hand that Uncertainty Decoding improves recognition performance, while on the other hand it is seen that the severe approximations needed to arrive at computationally tractable solutions have their noticable impact on recognition performance.

An analytic derivation of a phase-sensitive observation model for noise robust speech recognition - Leutnant, Volker; Haeb-Umbach, Reinhold (Interspeech 2009)
In this paper we present an analytic derivation of the moments of the phase factor between clean speech and noise cepstral or log-mel-spectral feature vectors. The development shows, among others, that the probability density of the phase factor is of sub-Gaussian nature and that it is independent of the noise type and the signal-to-noise ratio, however dependent on the mel filter bank index. Further we show how to compute the contribution of the phase factor to both the mean and the vari- ance of the noisy speech observation likelihood, which relates the speech and noise feature vectors to those of noisy speech. The resulting phase-sensitive observation model is then used in model-based speech feature enhancement, leading to significant improvements in word accuracy on the AURORA2 database.

A GPS positioning approach exploiting GSM velocity estimates - Peschke, Sven; Bevermeier, Maik; Haeb-Umbach, Reinhold (6th Workshop on Positioning Navigation and Communication (WPNC 2009))
A combination of GPS (global positioning system) and INS (inertial navigation system) is known to provide high precision and highly robust vehicle localization. Notably during times when the GPS signal has a poor quality, e.g. due to the lack of a sufficiently large number of visible satellites, the INS, which may consist of a gyroscope and an odometer, will lead to improved positioning accuracy. In this paper we show how velocity information obtained from GSM (global system for mobile communications) signalling, rather than from a tachometer, can be used together with a gyroscope sensor to support localization in the presence of temporarily unavailable GPS data. We propose a sensor fusion system architecture and present simulation results that show the effectiveness of this approach.
Keywords: cellular radio; distance measurement; global positioning system; Global Positioning System; global system for mobile communications; GPS positioning approach; GSM velocity; gyroscopes; gyroscope sensor; inertial navigation; inertial navigation system; odometer; sensor fusion system architecture; sensors

Verbesserung von GPS-basierter Ortung durch GSM-Geschwindigkeitsschaetzungen - Peschke, Sven; Bevermeier, Maik; Haeb-Umbach, Reinhold (DGON Navigationskonvent 2009)

Approaches to Iterative Speech Feature Enhancement and Recognition - Windmann, Stefan; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In automatic speech recognition, hidden Markov models (HMMs) are commonly used for speech decoding, while switching linear dynamic models (SLDMs) can be employed for a preceding model-based speech feature enhancement. In this paper, these model types are combined in order to obtain a novel iterative speech feature enhancement and recognition architecture. It is shown that speech feature enhancement with SLDMs can be improved by feeding back information from the HMM to the enhancement stage. Two different feedback structures are derived. In the first, the posteriors of the HMM states are used to control the model probabilities of the SLDMs, while in the second they are employed to directly influence the estimate of the speech feature distribution. Both approaches lead to improvements in recognition accuracy both on the AURORA2 and AURORA4 databases compared to non-iterative speech feature enhancement with SLDMs. It is also shown that a combination with uncertainty decoding further enhances performance.
Keywords: AURORA2 databases; AURORA4 databases; automatic speech recognition; feedback structures; hidden Markov models; HMM; iterative methods; iterative speech feature enhancement; model probabilities; speech decoding; speech enhancement; speech feature distribution; speech recognition; switching linear dynamic models

Parameter Estimation of a State-Space Model of Noise for Robust Speech Recognition - Windmann, Stefan; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this paper, parameter estimation of a state-space model of noise or noisy speech cepstra is investigated. A blockwise EM algorithm is derived for the estimation of the state and observation noise covariance from noise-only input data. It is supposed to be used during the offline training mode of a speech recognizer. Further a sequential online EM algorithm is developed to adapt the observation noise covariance on noisy speech cepstra at its input. The estimated parameters are then used in model-based speech feature enhancement for noise-robust automatic speech recognition. Experiments on the AURORA4 database lead to improved recognition results with a linear state model compared to the assumption of stationary noise.
Keywords: AURORA4 database; blockwise EM algorithm; covariance analysis; linear state model; noise covariance; noise-robust automatic speech recognition; noisy speech cepstra; offline training mode; parameter estimation; speech recognition; speech recognition equipment; speech recognizer; state-space methods; state-space model

Simulation of Ad Hoc Routing Protocols using OMNeT++ - Sommer, Christoph; Dietrich, Isabel; Dressler, Falko (Mobile Networks and Applications)

An evaluation of object oriented example programs in introductory programming textbooks - Börstler, Jürgen; S. Hall, Mark; Nordström, Marie; H. Paterson, James; Sanders, Kate; Schulte, Carsten; Thomas, Lynda (SIGCSE Bulletin)

Qualitätssicherung in einer interaktiven und lerneraktivierenden E-Learning-Umgebung - Schulte, Carsten; Tolksdorf, Robert (DeLFI Workshops)

Empirical comparison of objects-first and objects-later - Ehlert, Albrecht; Schulte, Carsten (ICER)

Bridging ICT and CS: educational standards for computer science in lower secondary education - Brinda, Torsten; Puhlmann, Hermann; Schulte, Carsten (ITiCSE)

Unterschiede im Lernerfolg von Schülerinnen und Sch\üern in Abhängigkeit von der zeitlichen Reihenfolge der Themen (OOP-First bzw. OOP-Later) - Ehlert, Albrecht; Schulte, Carsten (INFOS)

Informatik im Kontext (IniK) - Ein integratives Unterrichtskonzept für den Informatikunterricht - Koubek, Jochen; Schulte, Carsten; Schulze, Peter; Witten, Helmut (INFOS)

Dualitätsrekonstruktion als Hilfsmittel zur Entwicklung und Planung von Informatikunterricht - Schulte, Carsten (INFOS)

A simple instance-based approach to multilabel classification using the Mallows model - Cheng, W.; Hüllermeier, Eyke (In Proceedings MLD-2009 1st International Workshop on Learning from Multi-Label Data, Bled, Slovenia)

Learning pattern tree classifiers using a co-evolutionary algorithm - Senge, Robin; Hüllermeier, Eyke (in Proceedings 19th Workshop Computational Intelligence, Dortmund Germany)

Graph-kernels for the comparative analysis of protein active sites - Fober, T.; Mernberger, M.; Moritz, R.; Hüllermeier, Eyke (In Proceedings GCB-2009 German Conference on Bioinformatics Halle (Saale), Germany)

Learning pattern tree classifiers using a co-evolutionary algorithm - Senge, Robin; Hüllermeier, Eyke (In Proceedings Workshop LWA-2009, Lernen-Wissensentdeckung-Adaptivität, Darmstadt, Germany)

Extension and empirical comparison of graph-kernels for the analysis of protein active sites - Fober, T.; Mernberger, M.; Melnikov, Vitaly; Moritz, R.; Hüllermeier, Eyke (In Proceedings Workshop LWA-2009, Lernen-Wissensentdeckung-Adaptivität, Darmstadt, Germany)

Electron-Spin Beat Susceptibility of Excitons in Semiconductor Quantum Wells - Kwong, N. H.; Schumacher, Stefan; Binder, R. (Physical Review Letters)

Cross-Border Group-Taxation and Loss-Offset in the EU - An Analysis for CCCTB (Common Consolidated Corporate Tax Base) and ETAS (European Tax Allocation System) - Dahle, Claudia; Bäumer, Michaela

Der Einfluss der Abgeltungssteuer auf die Vorteilhaftigkeit von Anlagen in Genussscheine und Aktien - Halberstadt, Alexander; Sureth-Sloane, Caren; Voß, Armin (Die Wirtschaftsprüfung)

Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren

Umsatzsteuerausfall und Umsatzsteuerbetrug - Eine steuerökonomische Analyse der Umsatzsteuerdeklaration - Nordhoff, Daniel

Strukturprobleme angehen - Nordhoff, Daniel; Popp, Matthias (Niedersächsische Wirtschaft)

Verschärfung der Verlustabzugsbeschränkung durch § 8c KStG und deren Einfluss auf den Erwerb von Anteilen an Kapitalgesellschaften - Sureth-Sloane, Caren; Vollert, Pia

Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (Festzeitschrift für Franz W. Wagner: Accounting, Taxation, and Corporate Governance)

Information disclosure by answers to XPath queries - Böttcher, Stefan; Hartel, Rita (Journal of Computer Security)

Efficient construction of multiple geometrical alignments for the comparison of protein binding sites - Fober, T.; Klebe, G.; Hüllermeier, Eyke (in Proceedings ISDA-2009, 9th international Conference on Intelligent Systems Design and Applications, Pisa, Italy)

CSC: Supporting Queries on Compressed Cached XML - Böttcher, Stefan; Hartel, Rita (Database Technologies 2009, Twentieth Australasian Database Conference, ADC 2009)

XML Stream Data Reduction by Shared KST Signatures - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (2009 42nd Hawaii International Conference on System Sciences)

Similarity analysis of protein binding sites: A generalization of the maximum common subgraph measure based on quasi-clique detection - Boukhris, I.; Elouedi, Z.; Fober, T.; Mernberger, M.; Hüllermeier, Eyke (In Proceedings IDA-2009, 9th International Symposium on Intelligent Data Analysis, Pisa / Italy)

Fuzzy modeling of labeled point cloud superposition for the comparison of protein binding sites - Fober, T.; Hüllermeier, Eyke (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

A fuzzy variant of the Rand index for comparing clustering structures - Hüllermeier, Eyke; Rifqi, M. (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

Methoden und Werkzeuge für einen effizienten Ultraschallsensorentwurf - Henning, Bernd

Trends in ultrasonic transducer design - Henning, Bernd
Ultrasonic sensors are widespread in the process industry for example to measure flow, filling level, density or substance concentration in liquid mixtures today. On one side technically high demands are made to the ultrasonic sensors on the other side the production of the ultrasonic sensors has to be more and more cost-efficient. Today, these two contrary demands only can be met by the use of efficient development tools. This contribution describes the state of technology in the field of the computer-assisted ultrasonic transducer development, however, also shows the limits.

Ultrasonic Sensors for Process Applications - Sensor Design - Henning, Bernd; Rautenberg, Jens; Schröder, Andreas; Unverzagt, Carsten (Proceedings Sensor 2009)
Today, ultrasonic sensor systems are often applied in process technology. For the opening up of new industrial fields of application, such as the non-invasive process tomography, ultrasound sensors are necessary which are stable and adapted optimally under process conditions. Only with such optimized ultrasonic sensors the functionality of the sensor systems can be enlarged decisively with support of a complex measurement data evaluation. This contribution deals especially with the design process.

Computer assisted design of transducers for ultrasonic sensor systems - Henning, Bernd; Rautenberg, Jens; Unverzagt, Carsten; Schröder, Andreas; Olfert, Sergei (Journal of Measurement Science and Technology, MST)
In this contribution, possibilities and methods for computer-assisted design of ultrasound transducers are described. These transducers are essential for an ultrasonic sensor design, e.g. for continuous non-invasive determination of quantities that are important in process technology. To achieve technical reliability and robustness, the precise determination of all acoustic properties of the used sensor materials is of great importance. Problem-oriented modeling, numerical simulation, special optimization algorithms and improved methods for the visualization of propagating waves offer new and promising possibilities for developing ultrasonic transducers with enhanced properties.

Generating of short ultrasonic pulses using active damping - Rautenberg, Jens; Olfert, Sergei; Henning, Bernd
In non-destructive testing (NDT) with ultrasound the emission of short pulses is essentially if the echoes of nearby obstacles should be separated from the emitted signal. In this contribution a new approach is shown how to gene-rate a short ultrasonic pulse using a 3$-$1 composite transdu-cer. Therefore the ceramic bars, which are embedded in a polymer matrix, will be regarded as an exciter for the entire structure. After the pulse excitation the same bars can also be used for active damping to increase the bandwidth of the entire system. The Mason model serves as a basis for the de-scription of the ultrasonic transducer and is extended to the composite structure. The excitation signal is adaptively mo-dified by a suitable signal processing. Therefore the changes of boundary conditions, like the ambient temperature or acoustic impedance of adjacent media are considered.

Interdisciplinary Collaboration in a Visualization Course - Domik, Gitta (Informatics Education Europe IV, November)

Einsatz von Simulationswerkzeugen in der Entwicklungskette von ultrahochfesten warmgeformten Strukturkomponenten im Fahrzeugleichtbau* - Böke, Johannes; Erhardt, Rüdiger; Rostek, Wilfried; Tröster, Thomas (Materials Testing)

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, B.; Elser, D.; Bartley, Tim; Sabuncu, M.; Wittmann, C.; Sych, D.; Marquardt, C.; Leuchs, G. (Applied Physics B)

Merging chemical and biological space: Structural mapping of enzyme binding pocket space - Weskamp, N.; Hüllermeier, Eyke; Klebe, G. (Proteins)

FURIA: An Algorithm for unordered fuzzy rule induction - Hühn, J.; Hüllermeier, Eyke (Data Mining and Knowledge Discovery)

Why fuzzy decision trees are good rankers - Hüllermeier, Eyke; Vanderlooy, S. (IEEE Transactions on Fuzzy Systems)

Combining instance-based learning and logistic regression for multilabel classification - Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Fuzzy operator trees for modeling rating functions - Yi, Y.; Fober, T.; Hüllermeier, Eyke (International Journal of Computational Intelligence and Applications)

Evolutionary construction of multiple graph alignments for the structural analysis of biomolecules - Fober, T.; Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (Bioinformatics)

FR3: A fuzzy rule learner for inducing reliable classifiers - Hühn, J.; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Supporting case-based retrieval by similarity skylines: Basic concepts and extensions - Hüllermeier, Eyke; Vladimirskiy, I.; Prados Suarez, B.; Stauch, E. (Künstliche Intelligenz)

Optimal algorithms for page migration in dynamic networks - Bienkowski, Marcin; Byrka, Jaroslaw; Korzeniowski, Miroslaw; Meyer auf der Heide, Friedhelm (Journal of Discrete Algorithms)

An apparatus for the determination of speeds of sound in fluids - Gedanitz, Holger; Dávila, María J.; Baumhögger, Elmar; Span, Roland (The Journal of Chemical Thermodynamics)

Social Search: Exploring and Searching Social Architectures in Digital Networks - Trier, Matthias; Bobrik, Annette (IEEE Internet Computing)

Enabling social media content quality assurance using social network analysis - Sanmateu, Maria-Amparo; Trier, Matthias; Lienicke, Andreas; Rederer, Andreas (9th International Conference On Innovative Internet Community Systems I2CS 2010)

Content-based Community Detection in Social Corpora - Bobrik, Annette; Trier, Matthias (Proceedings Wirtschaftsinformatik)

Odp2cp – ein rapid E-Learning Ansatz zur einfachen Produktion Scorm-konformer Lerninhalte - Trier, Matthias; Herzog, Michael; Möller, Daniel (Proceedings Wirtschaftsinformatik)

Cooperation and coding framework - Biermann, Thorsten; Polgar, Zsolt Alfred; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Combining for cooperative WLANs-a reality check based on prototype measurements - Valentin, Stefan; Woldegebreal, Dereje H; Volkhausen, Tobias; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Improving network coded cooperation by soft information - Volkhausen, Tobias; Woldegebreal, Dereje H; Karl, Holger (Sensor, Mesh and Ad Hoc Communications and Networks Workshops, 2009. SECON Workshops' 09. 6th Annual IEEE Communications Society Conference on)

On the usefulness of fuzzy sets in data mining - Hüllermeier, Eyke (Views on Fuzzy Sets and Systems from Different Perspectives: Philosophy and Logic, Criticisms and Applications)

Statistics-based ID management for load balancing in structured P2P networks - Warneke, Daniel; Dannewitz, Christian (2009 IEEE 34th Conference on Local Computer Networks)

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, Guido (physica status solidi (c))

Vacancy clusters created via room temperature irradiation in 6H-SiC - Scholle, A.; Greulich-Weber, S.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physica B: Condensed Matter)

Decision tree and instance-based learning for label ranking - Cheng, W.; Hühn, J.; Hüllermeier, Eyke (in Proceedings ICML-2009, 26th International Conference on Machine Learning, Montreal, Canada)

Binary decomposition methods for multipartite ranking - Fürnkranz, J.; Hüllermeier, Eyke; Vanderlooy, S. (In Proceedings ECML/PKDD-2009, European Conference on Machine Learning and Principles and Knowledge Discovery in Databases, Bled Sloveniaery in Databases, Bled, Slovenia)

A new instance-based label ranking approach using the Mallows model. In Advances in Neural Networks - Cheng, W.; Hüllermeier, Eyke (in Proceedings 6th International Symposium on Neural Networks, Wuhan, China)

A Multithreaded Framework for Sequential Monte Carlo Methods on CPU/FPGA Platforms - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Towards Models for Many-Cores: The Case for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the Workshop on Many-Cores, International Conference on Architecture of Computing Systems (ARCS))

ARMLang: A Language and Compiler for Programming Reconfigurable Mesh Many-Cores - Giefers, Heiner; Platzner, Marco (Reconfigurable Architectures Workshop (RAW), Proceedings of the International Parallel and Distributed Processing Symposium)

Cooperative Multithreading in Dynamically Reconfigurable Systems - Lübbers, Enno; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

Program-driven Fine-grained Power Management for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

An adaptive Sequential Monte Carlo framework with runtime HW/SW repartitioning - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the 2009 International Conference on Field-Programmable Technology (FPT))

Proof-carrying Hardware: Towards Runtime Verification of Reconfigurable Modules - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))

Water adsorption on the α-Al2O3(0001) surface - Thissen, P.; Grundmeier, G.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Rare-earth defect pairs in GaN: LDA+U calculations - Sanna, Simone; Schmidt, Wolf Gero; Frauenheim, Th.; Gerstmann, Uwe (Physical Review B)

Adsorption structure of cyclopentene on InP(001)(2×4) - Passmann, Regina; Favero, Priscila; Schmidt, Wolf Gero; Miotto, Ronei; Braun, Walter; Richter, Wolfgang; Kneissl, Michael; Esser, Norbert; Vogt, Patrick (Physical Review B)

Role of Dihydrogen Bonds for the Stabilization of Self-Assembled Molecular Nanostructures - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)